Accelerating stem cell trials for Alzheimer's disease. Issue 2 (February 2016) - Hunsberger, Joshua G; Rao, Mahendra; Kurtzberg, Joanne; Bulte, Jeff W M; Atala, Anthony; LaFerla, Frank M; Greely, Henry T; Sawa, Akira; Gandy, Sam; Schneider, Lon S; Doraiswamy, P Murali
Summary: At present, no effective cure or prophylaxis exists for Alzheimer's disease. Symptomatic treatments are modestly effective and offer only temporary benefit. Advances in induced pluripotent stem cell (iPSC) technology have the potential to enable development of so-called disease-in-a-dish personalised models to study disease mechanisms and reveal new therapeutic approaches, and large panels of iPSCs enable rapid screening of potential drug candidates. Different cell types can also be produced for therapeutic use. In 2015, the US Food and Drug Administration granted investigational new drug approval for the first phase 2A clinical trial of ischaemia-tolerant mesenchymal stem cells to treat Alzheimer's disease in the USA. Similar trials are either underway or being planned in Europe and Asia. Although safety and ethical concerns remain, we call for the acceleration of human stem cell-based translational research into the causes and potential treatments of Alzheimer's disease.